Cultural Heritage and Value Creation: Towards New Pathways - Golinelli, Gaetano M (Springer, 2015)
Informed by systems thinking, this book explores new perspectives in which culture and management are harmoniously integrated and cultural heritage is interpreted both as an essential part of the social and economic context and as an expression of community identity. The combination of a multidisciplinary approach, methodological rigor and reference to robust empirical findings in the fertile field of analysis of UNESCO’s contribution mean that the book can be considered a reference for the management of cultural heritage. It casts new light on the complex relation of culture and management, which has long occupied both scholars and practitioners and should enable the development of new pathways for value creation.